The prospects of electricity generation from Poultry Processing Dewatered Sludge (PPDS) in Malaysia - Fadhil, M. (Trans Tech Publications Ltd, 2014)
Biomass today is considered a potential source of electricity generation in Malaysia under its National Renewable Energy Policy 2010. Among them, less attention has been paid to sludge waste even though its production is increasing. Therefore, the large amount of poultry processing dewatered sludge (PPDS) from a chicken-broiler-factory can be intensely analyzed and transformed to valuable fuel. From Malaysian PPDS, the preliminary findings reported in this paper are; a) ultimate analysis (Carbon; 55.68-67.38, Hydrogen; 7.61-9.81, Nitrogen; 3.28- 4.41, and Sulphur; 0.42-0.49), b) bomb calorimeter (heating value; 27-34 MJ/kg), c) moisture content; 69 - 74 and d) proximate analysis (Moisture content; 3, volatile matter; 77, fixed carbon; 8.31, and ash; 11). The usage of PPDS as an alternative fuel is costeffective and viable given by the high HHV relative to coal that is currently used in local power plants. The results from this study are expected to deliver a significant impact to both the poultry processing and the power generation industries based on the increasing poultry production trend in Malaysia. Â© (2014) Trans Tech Publications, Switzerland.